48‐3: Light Field Display Using Virtual Imaging Mode. Issue 1 (28th June 2021) - Fukano, Koichiro; Ito, Motoki; Shimizu, Misato; Kudo, Takaaki; Yura, Toshiki; Ichihashi, Koji; Takaki, Yasuhiro
Abstract : This study proposes a light field display (LFD) using a lens array and an aperture array. The viewing zone angle is larger for the proposed LFD than the LFDs using a lens array. The image brightness is higher for the proposed LFD than the LFDs using an aperture array.